2021
DOI: 10.1542/peds.2020-002444
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Emergency Department High-risk Bruising Screening Protocol

Abstract: OBJECTIVES: The objective of this study was to describe the outcomes of implementing a high-risk bruise screening pathway in a pediatric emergency department (ED). METHODS: A retrospective observational study was performed of children aged 0 to <48 months who presented to the ED between December 1, 2016, and April 1, 2019, and had bruising that is high-risk for physical abuse on a nurse screening examination. A high-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Continued reliance on the growing foundation of evidence-based literature and the creation of shared clinical guidelines for assessing child abuse concerns is important. To this end, ongoing work in the conception, validation, and implementation of clinical decision rules and artificial intelligence support in electronic medical records may be an avenue to mitigate the effect of implicit biases in the assessment of child physical abuse (Crumm et al, 2021; Pierce et al, 2021; Shahi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Continued reliance on the growing foundation of evidence-based literature and the creation of shared clinical guidelines for assessing child abuse concerns is important. To this end, ongoing work in the conception, validation, and implementation of clinical decision rules and artificial intelligence support in electronic medical records may be an avenue to mitigate the effect of implicit biases in the assessment of child physical abuse (Crumm et al, 2021; Pierce et al, 2021; Shahi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…14,15 given the known relationship between bruising in young infants and missed abuse. 5,16 However, many of the callbacks involved a lack of appropriate initial testing and sexual abuse and/or neglect, and 17% were from the clinic or inpatient setting.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that a significant proportion of young children with suspicious bruising was finally confirmed as victims of physical abuse. According to Crumm et al’s research [ 15 ] published in 2021, among the 43771 visitors to emergency departments who were screened for bruising, 163 (0.4%) had high-risk bruising according to the TEN4 FACESp rule. The rates of likely or definite abuse were 50% and 28% in children aged under 6 months and 6 months to 4 years, respectively.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…These findings emphasize the importance of minor wounds, such as bruising in abnormal regions of the body, for starting an investigation of possible child abuse. Moreover, in this study, the results showed that of 48 children aged 6 months or younger, 30 (63%) children underwent head computed tomography (CT) scans, and seven of these 30 (23%) children exhibited intracranial or head injury [ 15 ].…”
Section: Clinical Featuresmentioning
confidence: 99%